Relationship Between Parenting Self Efficacy and Parenting Stress on Parents to Support Early Children Playing at Home - Sugiana, Sugiana; Sasmiati, Sasmiati; Yulistia, Annisa (Indonesian Journal of Early Childhood Education Studies, 2020)
This research was motivated by the challenges of parents in taking care of their children when facing the coronavirus pandemic happening globally. This makes conditions change in various sectors. The implementation of â€œWork from Homeâ€ and â€œSchool from Homeâ€ is a government policy to break the chain of the coronavirus. The purpose of this research was to determine the relationship between parenting self-efficacy and parenting stress on parents to support early children playing at home. The research design was quantitative simple correlation. The population in this research were parents having young children in Bandar Lampung City. The sample of this research was selected by simple random sampling technique. The results showed that there was a significant negative relationship between parenting self-efficacy and parenting stress on parents in accompanying early childhood playing at home. So, if the parenting self-efficacy of parents is high, it can reduce the parenting stress when accompanying children to play at home. Based on these findings, this study suggests (1) further research should be done on a larger subject, (2) further research can compare between parents inservice and preservice training parenting, (3) Researchers can look for other factors as stressors for parents in parenting early childhood at home.